Tradisi Megibung dengan Menerapkan Protokol Kesehatan sebagai Atraksi Wisata Gastronomi di Era Normal Baru - I Nyoman Wiratnaya (JURNAL GASTRONOMI INDONESIA, 2020)
Megibung is one of the traditional ways to enjoy Karangasem specialties that serve various dishes such as: rice, various types of satay, lawar and other types of dishes. The way of eating is very unique, the number of participants is very interesting as a culinary tour. Megibung needs to be used as culinary tourism, most of the interviews strongly agree that megibung is used as culinary tourism. Megibung activities are usually carried out in a series of ceremonies. In this tradition, the element of togetherness, unity. Gibungan as a dish made through a food processing process and known as mebat needs to be modified according to the needs of tourists. Thus, the standard can be used as a cost reference as the need for a joint.